THE NEUROBIOLOGICAL BASIS OF SOCIAL BEHAVIOR: INSIGHTS FROM FUNCTIONAL IMAGING STUDIES - Ali Raza (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Social behavior is a fundamental aspect of human life, influencing interactions and decision-making processes within various societal frameworks. Understanding the neurobiological basis of social behavior has been a focus of research for decades, with significant advancements being made through functional imaging studies such as fMRI, PET scans, and EEG. These imaging techniques have revealed critical insights into how different brain regions interact to facilitate social cognition, empathy, emotional responses, and group dynamics. This paper reviews the latest findings in the neurobiology of social behavior, focusing on the neural substrates involved and the implications for mental health, particularly in the context of social disorders such as autism and schizophrenia.